Aesthetic salience and flow in young athletes: Exploring the moderating role of personality, gender, and age. (10th July 2018) - Coleman, Melanie J.; Barber, Bonnie L.; Donaghue, Ngaire
Abstract : Objective: This study investigated the relation between flow and aesthetic salience during sport, specifically whether heightened aesthetic salience interfered with flow for adolescent athletes. This study further tested whether neuroticism strengthened the relation between aesthetic salience and flow for boys and girls and whether this relation was stronger for year 9 or year 11 high school students. Method: Data were from wave two of the Youth Activity Participation Study (YAPS) of Western Australia. The sample included 1, 812 students (814 boys, 988 girls). The YAPS survey was administered using laptop computers or in pen and paper format. Results: Results indicated a significant four‐way interaction between aesthetic salience, gender, neuroticism, and year level for experiences of flow. Probing of the four‐way interaction indicated that aesthetic salience was positively predictive of flow at lower levels of neuroticism, but negatively predictive of flow at higher levels of neuroticism, for year 11 girls. For boys, there was a conditional main effect such that more experiences of aesthetic salience predicted more flow in sport. Conclusions: These findings illustrate that experiences of aesthetic salience in sport are complex and vary according to individual attributes.